2018
DOI: 10.5267/j.ijiec.2017.8.004
|View full text |Cite
|
Sign up to set email alerts
|

A simulated annealing algorithm for unequal area dynamic facility layout problems with flexible bay structure

Abstract: In this article, we propose Simulated Annealing (SA) heuristic to solve Unequal Area Dynamic Facility Layout Problem (FBS) with Flexible Bay Structure (UA-DFLPs with FBS). The UA-DFLP with FBS is the problem of determining the facilities dimension and their location coordinates with flexible bays formation in the layout for various periods of the planning horizon. The UA-DFLP with FBS is more constrained than general UA-DFLP and it is an NP-complete problem. The proposed SA is tested with the available UA-DFLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 35 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…Unlike other metaheuristics, SA is simple to implement, and is computationally more efficient one, but it gives a single solution for each run. Due to the simplicity in implementation of SA, many researchers applied SA to facility layout problems (Tam, 1992;Baykasoglu and Gindy, 2001;McKendall et al, 2006;Pillai et al, 2011;Kulturel-Konak and Konak, 2015;Hunagund et al, 2018;Moslemipour, 2018). In the present study also, SA heuristic is applied to solve the proposed robust approach UA-DFLP with FBS formulation.…”
Section: Dynamic Unequal Area Facility Layout Problem In Continuous Spacementioning
confidence: 97%
See 3 more Smart Citations
“…Unlike other metaheuristics, SA is simple to implement, and is computationally more efficient one, but it gives a single solution for each run. Due to the simplicity in implementation of SA, many researchers applied SA to facility layout problems (Tam, 1992;Baykasoglu and Gindy, 2001;McKendall et al, 2006;Pillai et al, 2011;Kulturel-Konak and Konak, 2015;Hunagund et al, 2018;Moslemipour, 2018). In the present study also, SA heuristic is applied to solve the proposed robust approach UA-DFLP with FBS formulation.…”
Section: Dynamic Unequal Area Facility Layout Problem In Continuous Spacementioning
confidence: 97%
“…This MILP model is based on the strategy of adaptive approach and is solved using GA and GAMS software. Hunagund et al (2018) developed a simulated annealing solution method to solve the adaptive approachbased MILP model of UA-DFLPs with FBS of Mazinani et al (2013). Hunagund et al (2018) reported better solutions using their SA than the solution of GA approach of Mazinani et al (2013).…”
Section: Dynamic Unequal Area Facility Layout Problem In Continuous Spacementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, meta-heuristic techniques have been extensively used for solving FLPs and, among them, genetic algorithms [2,19,23,35,44,49], simulated annealing [5,36,42], ant colony optimization [24,28,40,52], tabu search [8,30,33,54], particle swarm optimization [13,34], and coral reefs optimization [20].…”
Section: Introductionmentioning
confidence: 99%